The Relationship Between Body Mass Index (BMI) And Walking Speed in Users of SACH Foot Designed Transtibial Prosthesis - Cica Tri Mandasari Ningsih; Dody Suprayogi; Syarifah Syarifah (Poltekkes Kemenkes Palu, 2026)
Background: Walking speed is an important indicator for assessing mobility in prosthesis users. One factor suspected to influence walking speed is Body Mass Index (BMI). This study aims to determine the relationship between BMI and walking speed in transtibial prosthesis users with a SACH (Solid Ankle Cushion Heel) foot design. Methods: This observational study used a cross-sectional approach and was conducted at Klinik Bangkit Kaki Palsu from January to June 2025. A total of 15 subjects were purposively selected from a population of 40 patients who met the inclusion and exclusion criteria. BMI was calculated from body weight and height measurements, while walking speed was assessed using the 10-Meter Walk Test on a 14-meter walkway. Data normality was tested using the Shapiro-Wilk test, and the correlation analysis was performed using the Pearson product-moment test. Results: The majority of subjects were aged 26–35 years (53.3%), male (66.7%), and had a normal BMI (80%). The average walking speed between male and female subjects did not differ significantly. Statistical analysis revealed a significant correlation between BMI and walking speed, with a correlation coefficient of 0.590 and a p-value of 0.020 (p < 0.05), indicating a moderate positive relationship. Conclusion: This study found a significant relationship between BMI and walking speed among transtibial prosthesis users with a SACH foot design. These findings support the importance of considering BMI in prosthesis design and adjustment to enhance walking efficiency and user comfort.